The Role of Haptoglobin Genotypes in Chagas Disease. (23rd July 2014) - Mundaray Fernández, Ninomar; Fernández-Mestre, Mercedes
Abstract : Although the number of people infected with T. cruzi is on the rise, host genetic and immune components that are crucial in the development of the Chagas disease have been discovered. We investigated the frequency of polymorphisms in the gene encoding haptoglobin of patients with chronic Chagas disease. The results suggest that while the HP1-1 genotype may confer protection against infection and the development of chronic Chagas disease due to the rapid metabolism of the Hp1-1-Hb complex and its anti-inflammatory activity, the presence of HP2-2 genotype may increase susceptibility towards a chronic condition of the disease due to a slow metabolism of the Hp2-2-Hb complex, lower antioxidant activity, and increased inflammatory reactivity, which lead to cell damage and a deterioration of the cardiac function. Finally, correlations between HP genotypes in different age groups and cardiac manifestations suggest that HP polymorphism could influence the prognosis of this infectious disease. This study shows some of the relevant aspects of the haptoglobin gene polymorphism and its implications in the T. cruzi infection.